Avaliação técnica e financeira de recuperação de área degradada na região do Alto Teles Pires - Franco, Vinicius Correa (2022)
The objective of this work was to analyze the economic feasibility and technical efficiency of the recovery of a degraded area of the Cerrado with intensive use of the soil, interspersing the soybean crop with native forest species, characterized by an integration of crops, livestock and forest in recovery. The state of Mato Grosso is characterized as a major commodity exporter in Brazil, thus, large areas of native vegetation give space for the cultivation of crops, planted forests and livestock. Despite the technological efficiency and quality applied in modern agriculture, much of its native vegetation has been suppressed due to this expansion, increasing deforestation rates. However, the search for environmental regularization through the rural environmental registry (SIMCar) has been growing, and with that, the areas of legal reserve and permanent preservation areas to be recovered also grow. In this way, the development of an effective methodology to recover degraded areas that allows the financial return to the rural producer, using annual and perennial crops, in a system of intensive land use with mechanized management, is important for the maintenance of ecosystem services and producer's livelihood guarantee. In an area of approximately one hectare, lines of forest seedlings composed of nine native species were intercropped, totaling thirty-six seedlings per line, four lines per treatment, with a total of one hundred and forty-four seedlings distributed equally in an agroforestry system, among cultivars. agricultural (soybean) and control lines without any type of consortium. Over twelve months, mortality parameters, height, collar diameter, soil analysis before and at the end of the experiment and the economic viability of intercropping with agricultural cultivars were measured. The results showed the positive financial return of agricultural crops, allowing to mitigate the costs with the implementation and maintenance of forest seedlings for the recovery of the degraded area. They also showed the improvement of soil parameters, in the intercropped system and in the agroforestry, comparing the before and after the analyses. And they made it possible to recognize the species that developed better among treatments with lower mortality rates and greater growth. A better development of the seedlings inserted in the agroforestry system and intercropped with soybean was noticed and the soil cover in the integrated systems as a parameter of recovery of degraded area was efficient, avoiding exposed soil and invasion of unwanted species of high competitiveness.